Hindi Adaptation of Centrality of Religiosity Scale - Dua, Devakshi (Religions, 2020)
Although religiosity is part and parcel of life of most Indians, no standardized scale is available in local language which can make findings comparable with other countries’. This study aims to present the adaptations required in the Centrality of Religiosity Scale (CRS, CRSi-20) for the Indian population. Additionally, the study aimed to compare the religiosity as assessed by using CRS among healthy subjects and those with first-episode depression. CRS was translated to Hindi by following the methodology suggested by the World Health Organization. During the process of translation, the scale was adapted to suit to the sociocultural milieu of India. The adapted Hindi version of the scale was used in 80 healthy subjects and 80 patients with first-episode depression. During the process of translation, 14 out of 20 items required adaptations to suit the religious practices in India. The adaptation primarily involved elaboration on certain aspects of religious services and practices, keeping in mind the polytheistic religious beliefs in India. When the adapted Hindi version of CRS was used in both the study groups, there was no significant difference between the two groups, in terms of CRS total scores (t = 1.12; p = 0.26). In terms of various domains of CRS, a significantly higher score was observed in the depression group for the ideology domain (t = 2.02; p = 0.04 *), whereas the healthy group had a significantly higher score for the domain of public practice (t = 2.90; p = 0.004 **). Use of CRS in the Indian context requires some adaptations to suit the religious practices. There are minor differences in the religiosity of patients with depression and healthy subjects.